Store-and-Forward Tele-Dermatology Pilot Study in Belgium: Patients and Physicians Satisfaction Study With Process Evaluation - Annemie Heselmans; Bert Aertgeerts; Koen Roegies; Hilde Beele; Evelien Verhaeghe; An De Sutter; Nicolas Delvaux (International Journal of Clinical Practice)
Conclusions. The store-and-forward tele-dermatology system had the potential to allow a smooth transfer of high-quality dermatologic advice. Although there were differences between the dermatologists, the family physicians and the patients, general satisfaction with the system was high. There is a need for an extramural order management system in which the dermatologist could answer from his own electronic medical records.